Corona virus diseases - Rusul Ali Hassan Sayah; Raghad Lafta Hamound Ahmed; Mohammed Al-Bashir Jabbar Arhem; Sarah Hamed Hamid Antar; Dalia zuhair wael taha Alhitty (Genius Journals, 2024)
Coronaviruses are a major family virus( COVID-19). This is a highly infectious disease caused by the new Coronavirus (COVID-19) and can spread from person-to person through sneezing and coughing droplets. This virus has signs and symptoms similar to the common cold but is dangerous and if not reported early and managed by health workers it can cause severe illness in humans and can lead to death. Some coronaviruses cause disease in humans, and others in animals such as bats, camels, and cats. Human coronavirus usually causes mild illness, such as thecommon cold. (1)Animal coronaviruses rarely evolve to infect humans and spread among humans, causing severe illnesses such as Severe Acute Respiratory Syndrome (SARS), which appeared in 2002, and Middle East Respiratory Syndrome (MERS). MERS, which appeared in 2012. However, it can be difficult to determine the animal from which a coronavirus infection first starts spreading. In December last year, reports started to emerge that a coronavirus that specialists had never before seen inhumans had begun to spread among the population of Wuhan, a large city in the Chinese province of Hubei. (2) .Since then, the virus has spread to other countries, both in and outside Asia, leading the World Health Organization (WHO) to declare this as a pandemic. The COVID-19 pandemic, which has already infected nearly 170,000 people out of148 Countries, resulting in more than 6,500 deaths, 1 have the potential to reach a large number. The proportion of the world's population. Some estimates suggest 40-70 percent of The world population could be. It is hoped that it will succeed in reducing the transmission of nCoV-2019 and finding a treatment soon. In this paper, we try to explain more about this virus, the problems that caused for people and the methods used to diagnose COVID-19. (3)
Keywords: Corona; virus diseases; camels